The contribution of information and communication technologies (ICTs) in the growth of small and medium enterprises (SMEs) in Tanzania: A case of Urban district–Zanzibar - Merali, Mohamed Mohamed (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of the degree of Masters in Entrepreneurship Development (MSc.ENTR.) of Mzumbe University